Distribution of Human Capital Between Regions in Indonesia Using the Alternative Human Development Index - Windhani, Kikin; Mulyaningsih, Tri; Hardoyono, Fajar (KnE Social Sciences, 2022)
Human capital is an important factor in the development and economic growth of a country. This study aimed to (1) adopt a modified model of the Human Development Index (HDI) called the Alternative Human Development Index (AHDI) to measure human capital between regions in Indonesia, and (2) analyze the distribution pattern of human resource inequality between regions in Indonesia using cluster analysis. The results showed that the measurement of human capital with AHDI provided more comprehensive measurement results because it used a more complete dimension of human capital and showed the advantages and disadvantages of human capital between regions in Indonesia. The distribution of human capital inequality in Indonesia based on AHDI, using cluster analysis, showed that regions in Indonesia are divided into areas of high, medium, low and very low AHDI performance. The low and very low clusters are a priority for the government in the development of human capital in Indonesia. Keywords: human capital, gender empowerment, health index, democracy index, cluster analysis